Training in-service teachers: study of questions and the organization of teaching - Otero, Maria Rita (2020)
We analyse the study and research carried out by N = 31 teachers in service during an online course in Didactics of Mathematics, about a question that could generate a Study and research path (SRP). The teachers studied the question individually and in groups. Then, they had to organize a possible teaching, adapted to an institution well known to them .The written texts produced by the teachers are analysed by means of two types of techniques: one qualitative and one based on lexicometric statistical methods. In the long term, the aim of this research is to understand the potential and difficulties of in-service teachers to organize teaching based on questions.